Study protocol for a nested process evaluation of a complex discharge planning intervention (HOME Rehab) to improve participation after first-stroke - Reeder, Sandra; Stanley, Mandy; Jolliffe, Laura J.; Lannin, Natasha A. (Frontiers in Neurology, 2025)
IntroductionStroke is a leading cause of adult disability, and the transition from hospital to home can be fraught with challenges. The HOME Rehab trial is designed to address if better health outcomes for stroke survivors can be achieved with a contextually relevant and tailored occupational therapy discharge planning and support intervention. Process evaluations inform clinical trial findings and future scale up, as well as how to implement a successful intervention effectively into policy and practice. This paper describes the protocol we are using in the HOME Rehab process evaluation planning and activities.MethodsUsing a theoretically informed approach, mixed methods are being used to collect data and address all aspects of the RE-AIM framework. Quantitative data will comprise clinician surveys, trial logs and fidelity checklists as well as screening and recruitment numbers. Semi-structured interviews with trial participants and carers and focus groups with occupational therapists will provide qualitative data. A concurrent triangulation approach will be taken to draw on the strengths of multiple methods to cross-validate findings. The RE-AIM framework will be used to interpret the qualitative and quantitative data together as well as highlight areas of convergence or divergence in the findings. Multiple data sources will be integrated to refine the interpretation of outcomes, understand the context of program delivery, and identify key findings. Drawing on, and integrating data from, multiple perspectives and methods will strengthen the overall findings and provided detailed insights into the causal mechanisms as well as the contextual factors that may influence intervention outcomes.DiscussionProcess evaluations can optimize study outcomes by improving how a complex intervention is implemented, informing the actions of policymakers and clinicians. For the HOME Rehab intervention, the process evaluation may provide valuable data necessary to explain the trial findings, as well as inform future scale-up and implementation if the HOME Rehab intervention is shown to be effective.Clinical trial registrationhttps://www.anzctr.org.au, identifier ACTRN12618001360202.